1991
DOI: 10.1002/env.3770020205
|View full text |Cite
|
Sign up to set email alerts
|

Trend analysis methodology for water quality time series

Abstract: A general trend analysis methodology is developed for detecting and modelling trends in water quality time series measured in rivers and streams. The procedure is specifically designed for use with typically ill-behaved river quality series characterized by problematic features such as non-normal positively skewed populations, irregularly spaced instantaneous observations, seasonal periodicities, and dependence among water quality variables and riverflows. In order to analyze these "messy" environmental data i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0
5

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 21 publications
0
55
0
5
Order By: Relevance
“…To test this criterion, we proposed that QVI TS b /TS ub should exhibit a null T QVI . To test if T QVI was null, we proposed using the nonparametric Spearman Rank Correlation Test (Morettin and Castro Toloi 1987, McLeod et al 1991, Yue et al 2002.…”
Section: Proposed Criteria and Statistical Methodsmentioning
confidence: 99%
“…To test this criterion, we proposed that QVI TS b /TS ub should exhibit a null T QVI . To test if T QVI was null, we proposed using the nonparametric Spearman Rank Correlation Test (Morettin and Castro Toloi 1987, McLeod et al 1991, Yue et al 2002.…”
Section: Proposed Criteria and Statistical Methodsmentioning
confidence: 99%
“…The Mann-Kendall trend test approach is widely used in the analysis of various types of environmental data for testing monotonic trends [45,46]. The purpose of the Mann-Kendall (MK) testis to statistically assess if there is a monotonic upward or downward trend in the variable of interest over time [47].…”
Section: Mann-kendall Trend Testsmentioning
confidence: 99%
“…Man-Kendall test was suggested by Mann (1945) for randomness against time, which constitutes a particular application of Kendall's test for correlation commonly known as the 'Mann-Kendall' or the 'Kendall t test' (Kendall 1962). The test has been extensively used with environmental time series (Hipel & McLeod 1994, McLeod et al 1990). Let X 1 , X 2 ,……………X n represents data points over time, in the test null hypothesis H 0 is tested where the random variables are independent and identically distributed.…”
Section: Mann-kendall Testmentioning
confidence: 99%
“…Most of these studies have shown that the trend of temperature or precipitation distribution of a particular region is either decreasing or increasing. A recent study by Karl et al (1993) have shown that the monthly minimum temperature, from countries comprising 37% of the global landmass, is increasing by 0.84 o C compared to only 0.28 o C increase in maximum temperature for the period 1951-1990 report has also demonstrated that the global surface warming is occurring at a rate of 0.74±0. 18 °C during 1906-2005.…”
Section: Introductionmentioning
confidence: 98%